Socio-Psychological Drivers of Livelihood Diversification in Lakshadweep - Anshida Beevi , Monika Wason , R. N. Padaria , N.V. Kumbhare; Eldho Varghese (Indian Journal of Extension Education, 2015)
Diversification is the incorporation of new activities into the economic portfolio. The rural livelihood diversification therefore is an integral dimension of development agenda for strengthening rural livelihood and sustaining livelihood security. The study was conducted among 120 households in Kalpeni and Andrott islands of U.T. of Lakshadweep to assess the extent of diversification and to analyse the socio-psychological factors promoting diversification. Respondents were randomly selected and categorized into three livelihood classes based on the share of agriculture in households’ income. Extent of livelihood diversification is studied in terms of number of income sources of a household and Simpson index of diversification. It is obtained that most of the households were having diverse livelihood strategy. It has been found that majority of the diversified households have medium diversification index with average diversification index of 0.32. Determinants of diversification were analyzed using Kruskal-Wallis test. It was found out that mass media exposure was the most significant factor leading to diversification followed by social participation, change proneness and achievement motivation.